AN ANALYSIS OF TRAFFIC ACCIDENT RATES ON THE UJUNG TANJUNG–BAGAN SIAPI API ROAD SECTION (KM 6–KM 60), ROKAN HILIR REGENCY, RIAU PROVINCE - Abdul Kudus Zaini; Rahmad Kurnia; Vella Anggreana (PT. Intelek Cendikiawan Nusantara, 2024)
Traffic accidents are unforeseen and unintentional incidents involving vehicles or other road users, leading to human casualties (including minor injuries, serious injuries, or fatalities) and property damage. This study aims to analyze accident rates by examining contributing factors such as causative elements, accident black spots, and the impact of road user characteristics, including age, occupation, and driver condition. The research employed an observational method, involving direct field surveys along the Ujung Tanjung–Bagansiapiapi road section in Rokan Hilir. The findings revealed that human factors were the predominant cause of accidents, accounting for 61 incidents, while road-related factors contributed to 5 accidents. The age group most affected by accidents was 21–25 years, which resulted in 25 fatalities. Additionally, the study identified two critical black spots: the Jumrah Ujung Tanjung section, with an accident rate of 0.310, and the Tanah Merah Jumrah section, with an accident rate of 0.274. To mitigate accident rates, it is crucial to enhance road safety by installing traffic signs and other supporting infrastructure.